Maternal employment and the care of school-aged children - Hand, Kelly; Baxter, Jennifer (My University, 2013)
Children’s participation in both formal and informal child care is often a necessity in families of school-aged children when parents are employed. This mixed methods paper describes links between maternal employment and use of different types of child care for school-aged children, incorporating findings from the Family and Work Decisions qualitative study, and analyses of survey data from the Longitudinal Study of Australian Children. The paper explores factors involved in mothers’ decision-making about employment as well as child care, with key concerns being related to the availability of different care providers, the flexibility of their own employment and children’s capacity for self-care. The data are also used to examine which families use particular care arrangements for school aged children, with a focus on how care arrangements vary for mothers working in different types of jobs. Informal care arrangements are examined as well as formal care arrangements.
Keywords: Families and relationships; Families and relationships